Short S=O center dot center dot center dot C=O contacts associate diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate in their inclusion complexes - Manoj, Kochunnoonny; Sureshan, K. M.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Crystal Growth & Design, 2005)
Diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate are linked via short S=O&BULL;&BULL;&BULL; C=O contacts ranging from 2.890 to 3.140 &ANGS; (sum of the van der Waals radii of O and C atoms 3.22 &ANGS;) in all the inclusion complexes formed with organic guest solvents having a C2 symmetry. Although a search for S= O&BULL;&BULL;&BULL; C=O interactions in the CSD showed a sizable number of structures, this communication recognizes its significance for the first time in the formation of molecular assemblies. In all the crystals in the present study except the solvent-free form, the S=O bond points almost perpendicularly to the Csp2 atom of the C=O group. This was also the most frequently observed geometrical approach in CSD analysis. The solvent-free form shows dimer formation via C-H&BULL;&BULL;&BULL; O interaction, which has longer S=O&BULL;&BULL;&BULL; C=O contacts.